Carbon microsphere-templated synthesis of ZnCo2O4 hollow spheres functionalized with Ag nanoparticles for sub-ppm-level acetone gas detection. Issue 10 (July 2020) - Zhang, Dongzhi; Jin, Yingbo; Chen, Haonan; Luo, Yuwei; Zhang, Yong
Abstract: This paper demonstrated a high-performance acetone sensor based on sensing material of ZnCo2 O4 @Ag hollow spheres (HSs) was prepared using carbon microsphere as sacrifice template. The ZnCo2 O4 @Ag HSs film was coated on a ceramic tube with two Au electrodes, and the nanostructure of ZnCo2 O4 @Ag HSs was examined by XRD, EDS, SEM, TEM and XPS techniques. The gas sensing investigation was performed under different working temperatures (120–320 °C) for the ZnCo2 O4 @Ag sensors with different Ag loading amount. The results show that the ZnCo2 O4 @Ag (2 wt%) based sensor yields excellent acetone-sensing performance at 220 °C, such as low detection limit (0.25 ppm), fast response/recovery properties (4 s/20 s@0.25 ppm), and good selectivity. The excellent acetone-sensing performance benefits from the p-type semiconductor properties of ZnCo2 O4 and the catalysis of Ag nanoparticles. This work confirmed that the ZnCo2 O4 @Ag (2 wt%) based sensor has promising applications for highly sensitive and selective acetone detection in various fields.